Understanding Digital Innovation in Bank Papua: The Influence of Digital Organizational Culture Through Organizational Readiness - Rini Juni Astuti; Ega Mawarni Siregar (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the effect of Digital Organizational Culture on Digital Innovation with Organizational Readiness as a mediating variable among employees of Bank Papua in Merauke City. This study uses a quantitative approach with a survey method. Primary data were collected through an online questionnaire using Google Form distributed to all employees of Bank Papua in Merauke City. The sampling technique used was saturated sampling (census) with a total of 140 employees as respondents. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4, covering validity and reliability tests, structural model testing, and hypothesis testing. The results show that Digital Organizational Culture has a positive and significant effect on both Digital Innovation and Organizational Readiness. Organizational Readiness is also proven to have a positive and significant effect on Digital Innovation, and significantly mediates the effect of Digital Organizational Culture on Digital Innovation. The conclusion of this study indicates that the success of digital innovation is determined not only by digital organizational culture, but also strongly depends on the level of organizational readiness, both in terms of human resources, technology, and work processes. Therefore, banking organizations need to simultaneously strengthen digital culture and improve organizational readiness in order to drive sustainable digital innovation.